PENINGKATAN HASIL BELAJAR SISWA KELAS V DALAM PEMBELAJARAN IPS BERBANTUAN GAMES BOOK - Distia Hilma Damayanti; Erik Aditia Ismaya; Ahmad Bakhruddin (STKIP Subang, 2023)
This classroom action research was motivated by the low social studies learning outcomes of fifth grade students at SDN 1 Kedungdowo. In this case, researchers use the Games Book media as an improvement in learning outcomes in Class V in Social Sciences lessons. This study uses the PTK method, which consists of two cycles. Each cycle consists of stages namely planning (planning), implementation of action (acting), observation (observing) and reflection (reflecting). Data collection techniques using interviews, observation, tests and documentation. Data analysis techniques which include data reduction, presentation and drawing conclusions. The results showed that the teacher's teaching skills increased by an average of ≥75%. In the first cycle, the percentage was 72.82% and the second cycle increased with the percentage to 80.97% with good and successful criteria. Student learning outcomes increased by an average of ≥75% classical. The percentage of the completed cycle I obtained 56.67% and the completed cycle II obtained 76.67%.